Light-stable polypyridine silver(i) complexes of 1, 3, 5-triaza-7-phosphaadamantane (PTA) and 1, 3, 5-triaza-7-phosphaadamantane-7-sulfide (PTAS): significant antiproliferative activity of representative examples in aqueous media. Issue 30 (25th June 2019) - Jaros, Sabina W.; Śliwińska-Hill, Urszula; Białońska, Agata; Nesterov, Dmytro S.; Kuropka, Piotr; Sokolnicki, Jerzy; Bażanów, Barbara; Smoleński, Piotr
Abstract : A series of novel silver polypyridine complexes containing PTA or PTAS have been synthesized and fully characterized. Representative light-stable and water-soluble complexes were evaluated for their cytotoxic and the antitumor activity. Abstract : A series of novel silver(i ) 2, 2′:6′, 2′′-terpyridine (tpy), 4′-(4-methylphenyl)-2, 2′:6′:2′′-terpyridine (tpy-Ph-Me) and 1, 10-phenanthroline-5, 6-dione (dione) derivatives containing PTA (1, 3, 5-triaza-7-phosphaadamantane) or 1, 3, 5-triaza-7-phosphaadamantane-7-sulfide (PTAS) have been synthesized and fully characterized. Two types of complexes have been obtained, monocationic [Ag(tpy)(PTA)](NO3 ) (1 ), [Ag(tpy-Ph-Me)(PTA)](NO3 ) (2 ), [Ag(dione)(PTAS)](BF4 ) (4 ) and [Ag(dione)2 ](PF6 ) (5 ) and neutral [Ag(dione)(PTAS)(NO3 )] (3 ). The solid-state structures of four complexes have been determined by single-crystal X-ray diffraction. Complexes1 and2 are luminescent at room temperature and 77 K while5 shows emission only at 77 K. Compounds3 and4 are not emissive. Furthermore, representative light-stable and water-soluble1 and3 were evaluated for their cytotoxic activities on the normal human dermal fibroblast (NHDF) cell line and their antitumor activity using the human lung carcinoma (A549), epithelioid cervix carcinoma (HeLa) and human breast adenocarcinoma (MCF-7) cell lines. Interactions between the complexes and human serum albumin (HSA) using UV-Vis, fluorescence and circular dichroism spectroscopy (CD) were also investigated.